3, 3′‐Diiodo‐BINOL‐Fused Maleimides as Chiral Hypervalent Iodine(III) Organocatalysts. Issue 36 (15th November 2013) - Brenet, Simon; Berthiol, Florian; Einhorn, Jacques
Abstract: Original and readily available 3, 3′‐diiodo‐BINOL‐fused maleimides were designed as hypervalent iodine(III) organocatalysts. They were used in intermolecular oxidation reactions at the α‐position of ketones. The expected products were obtained with yields and enantiomeric excesses that were comparable to the best reported values achieved using structurally different organocatalysts. Abstract : New 3, 3′‐diiodo‐BINOL‐fused maleimides were designed as hypervalent iodine(III) organocatalysts and were easily synthesized in a few steps and in high yields. Their use as catalysts in the benchmark α‐tosylation of ketones resulted in yields and enantiomeric ratios that were among the best reported.